Optically induced motion of liquid crystalline droplets. Issue 40 (13th September 2018) - Dogishi, Yoshiharu; Sakai, Yota; Sohn, Woon Yong; Katayama, Kenji
Abstract : Rolling motion is activated by UV light for photo-responsive nematic droplets in a surfactant solution. Abstract : The controlled motion of a liquid crystalline active droplet was demonstrated in a surfactant solution and by irradiation with UV light. The droplet could be induced to roll on a glass substrate toward the UV light source. This was explained by the Marangoni flow induced by the UV-induced desorption of surfactants.